A review of rockburst: Experiments, theories, and simulations - He, Manchao; Cheng, Tai; Qiao, Yafei; Li, Hongru (Journal of Rock Mechanics and Geotechnical Engineering, 2023)
Rockburst is becoming a huge challenge for the utilization of deep underground space. Extensive efforts have been devoted to investigating the rockburst behavior and mechanism experimentally, theoretically, and numerically. The aim of this review is to discuss the novel development and the state-of-the-art in experimental techniques, theories, and numerical approaches proposed for rockburst. The definition and classification of rockburst are first summarized with an in-depth comparison among them. Then, the available laboratory experimental technologies for rockburst are reviewed in terms of indirect and direct approaches, with the highlight of monitoring technologies and data analysis methods. Some key rockburst influencing factors (i.e. size and shape, rock types, stress state, water content, and temperature) are analyzed and discussed based on collected data. After that, rockburst theories and mechanisms are discussed and evaluated, as well as the microscopic observation. The simulation approaches of rockburst are also summarized with the highlight of optional novel numerical methods. The accuracy, stability, and reliability of different experimental, theoretical and numerical approaches are also compared and assessed in each part. Finally, a summary and some aspects of prospective research are presented.